2009
DOI: 10.1007/s12070-009-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening for hearing loss: pilot study from a tertiary care centre

Abstract: Many developed countries have well established universal neonatal hearing screening programs. In India, the viability of such a program, in an already overburdened health system is indeed a challenge. This cross sectional study was undertaken to evaluate the possible burden of hearing loss among neonates born at a tertiary care hospital in Southern India. Five hundred neonates were screened with automated distortion product otoacoustic emission (aDPOAE) for hearing loss, 9.2% of whom had one or more high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 9 publications
4
39
0
Order By: Relevance
“…John et al had shown refer rate of initial test of 6.4 % was reduced to 1.6 % on subsequent tests [16]. In present study refer rate of initial study of 10 % was reduced to 1 % on subsequent follow up tests.…”
Section: Group B 25%supporting
confidence: 40%
See 1 more Smart Citation
“…John et al had shown refer rate of initial test of 6.4 % was reduced to 1.6 % on subsequent tests [16]. In present study refer rate of initial study of 10 % was reduced to 1 % on subsequent follow up tests.…”
Section: Group B 25%supporting
confidence: 40%
“…According to John et al, 2009, low birth weight was the most common risk factor in high risk babies, which accounts for 26 (56.52 %) out of 46 high risk babies [16]. Babies admitted to a neonatal intensive care unit for more than 48 h are 10.2 times more likely to have a permanent hearing loss than those who did not undergo Meningitis-most common cause of acquired hearing loss is childhood meningitis.…”
Section: Group B 25%mentioning
confidence: 99%
“…History of blood exchange due to Hyperbilirubinemia and positive family history were not significantly different between two groups. Our OAE refers rate in comparison to the study conducted in Thailand [exclude NICU admission] (6.1%) [6], India (6.4%) 7 and Spain (6.7%) 8 on one side and Brazil(25.3%) 9 , the U.S (2.3%) 10 and Babol,Iran (10.8% ) 21 on the other side; refer rate variation may be explained by the number of births per year in each center of the screening 10 and age in which the first OAE was carried out which may be affected by debris or buid in the external or middle ear in early infancy 7,11 . However, this rate should not exceed upper limit defined by JCIH who recommended that failures in the first stage screening should not surpass 10% 12 .…”
Section: Discussionmentioning
confidence: 61%
“…Although OAE screening is quicker, easier and more cost-effective to perform than the ABR, it may be affected by debris or ûuid in the external or middle ear resulting in referral rates of 5 to 20% when screening is performed between the ûrst 24 hours of life 7,11 ABR screening requires the infant to be in a quiet state, but it is not affected by middle or external ear debris. Referral rates lower than 4% may be achieved when OAE is combined with automated ABR in a two-step screening system 11 Since OAE is quick and cost effective compared to ABR, retesting with OAE makes the universal screening program more feasible especially when there are large numbers of newborns and low financial support, as in developing countries 7 . In the present study, the main risk factors for hearing loss were history of NICU admission, followed by low birth weight (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to John et al (6.4%) and Gouri et al (5.30%). 15,16 But it contradicts Nagapoornima et al findings. 17 She did a similar study of screening for 279 high risk south Indian babies and reported a 1% prevalence rate of hearing impairment.…”
Section: Discussionmentioning
confidence: 65%